Paraoxonases (PON) 1, 2, and 3 Polymorphisms and PON-1 Activities in Patients with Sickle Cell Disease - Cadiele Oliana Reichert; Carolina Garcia de Macedo; Débora Levy; Bruno Carnevale Sini; Andréia Moreira Monteiro; Magnus Gidlund; Luciana Morganti Ferreira Maselli; Sandra Fátima Menosi Gualandro; Sérgio Paulo Bydlowski (MDPI AG, 2019)
(1) Background: Oxidative stress, chronic inflammation, vasoocclusion, and free iron are all features present in sickle cell disease. Paraoxonases (PON) are a family (PON-1, PON-2, PON-3) of antioxidant enzymes with anti-inflammatory action. Here, for the first time, we described PON-1 activities and PON-1, PON-2, PON-3 polymorphisms in patients with sickle cell disease, homozygous for HbSS, compared with healthy controls. (2) Methods: The groups were matched for age and gender. PON-1 activities (arylesterase and paraoxonase) were determined by enzymatic hydrolysis of phenylcetate and paraoxon, respectively. Polymorphisms were determined by Restriction Fragment Length Polymorphism- Polymerase Chain Reaction (RFLP-PCR). (3) Results: Plasma cholesterol and fractions, ApoA1 and ApoB levels were all decreased in sickle cell disease patients, while anti-oxidized low-density lipoprotein (LDL) antibodies and C-reactive protein were increased. Serum arylesterase activity was lower in sickle cell disease patients when compared with healthy controls. In patients, paraoxonase activity was higher in those with PON-1 RR Q192R polymorphism. In these patients, the increase of serum iron and ferritin levels and transferrin saturation were less pronounced than those observed in patients with QQ or QR polymorphism. No differences were observed with PON-1 L55M, and PON-2 and PON-3 polymorphisms. Multivariate regression analysis showed that transferrin and ferritin concentrations correlated with arylesterase and paraoxonase activities. (4) Conclusions: Both transferrin and ferritin were the main predictors of decreased arylesterase and paraoxonase activities in patients with sickle cell disease. LDL oxidation increased, and RR PON-1 Q192R polymorphism is likely to be a protective factor against oxidative damage in these patients.